An Attempt to Shift Commodified Archaeological Practices in Taiwan through Community Engagement - Bo-Chiao 王柏喬, Wang; Kuo-Feng 鍾國風 , Chung; Zorzin, Nicolas (Ex Novo: Journal of Archaeology, 2021)
Archaeological practice in Taiwan, an island located in East-Asia, is deeply influenced by Han Chinese culture and by the implementation of capitalistic approaches to dealing with archaeology that developed thanks to the ideological influence of the United States or the United Kingdom. This article aims to introduce a case study of an experimental approach to public archaeology carried out in Taiwan, which invested substantial effort to being self-reflexive. Since the 1980s, archaeological practice and the preservation of archaeological heritage in Taiwan has been practiced within the framework of contract archaeology. However, although the number of instances of commercial archaeology increased exponentially, the number of trained archaeologists remains scarce. In this context, archaeologists were trapped within an extractivist economic system that only served the interests of developers. Overwhelmed by massive amounts of work, the quality of the archaeological practice inevitably decreased. In reaction, some archaeologists are now seeking an alternative by adopting more reflexive approaches, which include public archaeology and community engagement. This article presents a brief introduction to the development of cultural heritage, archaeology, and public archaeology in Taiwan, followed by a case study from the site of the Old City of Zuoying (zuoying jiucheng, 左營舊城) (Southern Taiwan). By sharing our experiences, we aim to emphasise the significant positive aspects that emerged from a community-based and experimental approach, but at the same time to highlight the difficulties and failures we faced with this approach.